Development of Organizational Leadership in the Implementation of Comprehensive Leadership Pipeline towards Organization - Heni Susilowati; Erwan Nur Hidayat; Nindi Anggi Wardani; Kasih Purwanti (Journal of Management and Informatics, 2022)
This research examines the potential for leadership development through the creation of comprehensive leadership channels within organizations. By highlighting training elements that focus on the skills required for success in a leadership role) and succession planning (i.e., the creation and implementation of long-term plans that address changes in top leadership roles) as two distinct organizational initiatives. The method in this research is to combine the concept of Real Option Reasoning (ROR) with a skill-based leadership model. An in-depth study of the implementation of Comprehensive Leadership Pipelines (CLP) as an alternative to developing a leadership model is also reviewed in this study. The conclusion of this study is that by adjusting succession planning policies to outreach organizations according to the ROR pillars, it is possible to create CLPs that simultaneously lower turnover, increase the likelihood that employees will be in the right place at the right time, and reduce the risks associated with large investments. on employees. Given the need for organizations and individuals to assist in the selection of employees for appropriate leadership skills-based training, companies can make better and less risky decisions when selecting organizational leaders.